Impact of the Social Rehabilitation Program for Uninhabitable Houses (RS-Rutilahu) in Improving the Quality of Life in Banjarmasin City - Rachma, Maulida; Hidayat, Yusuf; Mahyuni, Mahyuni (International Journal of Multidisciplinary Approach Research and Science, 2024)
The city of Banjarmasin, situated in the heart of South Kalimantan Province, has grappled with significant challenges concerning uninhabitable houses. In its endeavor to address this issue, the Banjarmasin City Government is implementing concerted efforts to combat poverty by renovating uninhabitable homes. This research aims to analyze the impact of the Social Rehabilitation Program for Uninhabitable Houses (RS-Rutilahu) on improving the quality of life for the community in Banjarmasin City. The research follows a descriptive qualitative approach, engaging in activities that direct the exploration and in-depth examination of the social aspects under investigation. The research results indicate that the Social Rehabilitation Program for Uninhabitable Houses (RS-Rutilahu) has yielded positive impacts on various factors: (1) the health sector; (2) the education sector; (3) the economy; (4) the security sector; and (5) the socio-cultural field. This program has demonstrated its effectiveness in enhancing the quality of life in the City of Banjarmasin and mitigating poverty, which stands as the primary developmental challenge in the city.